Interaction of Finger Representations in the Cortex of Individuals with Autism: A Functional Window into Cortical Inhibition. Issue 6 (27th August 2013) - Coskun, Mehmet A.; Loveland, Katherine A.; Pearson, Deborah A.; Papanicolaou, Andrew C.; Sheth, Bhavin R.
<x xml:space="preserve">Abstract</x> An established neural biomarker of autism spectrum disorder (ASD) has the potential to provide novel biological and pharmacological targets for treatment. Lower level of inhibition in brain circuits is a leading biomarker candidate. A physiological investigation of the functional levels of inhibition in the cortex of individuals with autism can provide a strong test of the hypothesis. The amplitude of cortical response to the stimulation of adjacent fingers is controlled by the level of cortical inhibition and provides just such a test. Using magnetoencephalography, we recorded the response of the somatosensory cortex to the passive tactile stimulation of the thumb (D1), and index finger (D2), and to the simultaneous stimulation of both fingers combined (D1, D2) of the dominant (right) hand of young subjects with and without autism. For each participant, we measured the response to the stimulation of both fingers combined (D1, D2) relative to the post hoc sum of the responses to the stimulation of each finger alone (D1+D2) in multiple different ways and linearly regressed the ASD and neurotypical (NT) groups' responses. The resulting slopes were then compared: Smaller slope values imply attenuated response to paired finger stimulation, and enhanced levels of inhibition. The short‐latency M40 and mid‐latency M80 response slopes of the group with autism obtained in different ways were either significantly smaller, or statistically indistinguishable from NT. The result does not support reduced inhibition in the somatosensory cortex of individuals with autism, contrary to the seminal hypothesis of reduced inhibition. Implications are discussed including refinements of current theory. Autism Res 2013, 6: 542–549. © 2013 International Society for Autism Research, Wiley Periodicals, Inc.